Methodological Aspects of Linear Analysis of Vegetation Cover Nonlinear Structure (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
Question: How to apply linearization in vegetation science on the example of using the method of synphytoindication to assess the conditions of plant communities existence. Locations: Carpathians, Shatsk National Nature Park, Slovechansko- Ovruchsky Ridge, Cherkasy-Chyhyryn Geobotanical District, Kyiv Forest Plateau, Central Podilsky Geobotanical District, Dniester Canyon, Krasna River Basin, Mountain Crimea. Methods: For the analysis, we used generally accepted biometric statistical methods, as well as original author's methods. Nomenclature: POWO 2023 Results: Linearization is a method of simplifying complex nonlinear relationships to linear forms of a certain type. This is one of the effective approaches to assessing the nonlinear structure, behavior, modeling, and forecasting the development of phytocenoses based on modern mathematical approaches and methods. From a methodological point of view, linearity could be interpreted as a projection of a non-linear structure from a multidimensional space onto planes on which lines have a certain shape, length and direction, that is, vectorization. At the same time, there are problems regarding the adequacy of displaying the results and not distorting the essence, which requires checking the results by different methods of calculations and different representativeness of the data, as well as finding limits. The paper gives examples of linearization from various areas of phytocenology. When evaluating the representativeness of the sample of relevés of alliances for phytoindication by different calculation methods, we found that the use of 30 relevés from different associations gives reliable results, and the reliability is high when using 50 relevés. Step-by-step manipulation of average values, in the comparative analysis of the syntaxonomic composition at the landscape or regional level, that is, the assessment of β, γ-diversity increases the level of reliability of approximation and visualization. Analysis examples of the complex character of the correlations between the ecological indicators shows that in some cases qualitative changes occur outside the critical limits, at the bifurcation points, which indicates the need to take into account the limiting values when developing prognostic models. Conclusions: We concluded that the reliability of the results obtained by only one method is not reliable enough, but needs to be checked by another calculation method or evaluation of another sample of data. The given examples testify to the perspective of the linearization approach in geobotanical research.
Keywords: linearization, method, ordination, representativeness of the sample, synphytoindication, syntaxa, the mean value, vegetation.